2018
DOI: 10.4236/psych.2018.94046
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Spirituality and Religiosity in Type 2 Diabetes Mellitus Management—A Systematic Review

Abstract: Background: There has been significant argumentation whether spirituality/religiosity directly affect(s) type 2 diabetes mellitus (T2DM) outcomes and well-being. Objectives: To evaluate the impact of spirituality/religiosity on T2DM management. Data sources: The PubΜed database was searched thoroughly for relevant papers. Results: The results show a positive relation between religiosity/spirituality and improved T2DM management. Limitations: The nature of the studies included is mostly qualitative and limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 66 publications
0
30
0
3
Order By: Relevance
“…Regression analysis yielded religious congregations per 1000 accounted for 29.1% of the variance associated with more adult diabetes, whereas non-religious non-profit organizations per 1000 accounted for 23.4% associated with less adult diabetes. Religious congregations per 1000 proves contrary to the narrative in existing social capital research where religious congregations and affiliations are linked with better glycemic control and healthier lifestyles; religious congregations serve as a support system and educational system for their parishioners ( Darvyri, 2018 , p. 1). It is to no surprise that non-religious non-profit organizations per 1000 were associated with less adult diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…Regression analysis yielded religious congregations per 1000 accounted for 29.1% of the variance associated with more adult diabetes, whereas non-religious non-profit organizations per 1000 accounted for 23.4% associated with less adult diabetes. Religious congregations per 1000 proves contrary to the narrative in existing social capital research where religious congregations and affiliations are linked with better glycemic control and healthier lifestyles; religious congregations serve as a support system and educational system for their parishioners ( Darvyri, 2018 , p. 1). It is to no surprise that non-religious non-profit organizations per 1000 were associated with less adult diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…In a systematic review of the role of religiosity in T2D management, religiosity was associated with lowered rates of depression and stress, especially in women of low socioeconomic status, which could lead to improved management behaviors. 17 However, no le doy mente may also be used as an avoidance or emotion-focused coping strategy, especially when framed within religious beliefs connected with fate. For example, Mariana's story about not seeking care for her injured foot because she left the outcome in God's hands illustrated that no le doy mente may hinder timely care.…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 systematic review found a positive relationship between patient spirituality or religiosity and improved management of T2DM (Darvyri et al 2018). Spiritual practices, such as regular prayer, scripture reading, or communal worship, improved patient emotional adjustments to diagnosis, psychological endurance with chronic disease, mental health (including reduced depression and anxiety), glycaemic control, and quality of life (QoL) (Heidari et al 2017;Darvyri et al 2018).…”
Section: Spirituality Mental Wellness and Diabetes Carementioning
confidence: 99%